Tenant Work Order Decision Support System Analytical Hierarchy Process (AHP) Method Based on Java Netbeans in Midplaza Building: Tenant Work Order Decision Support System Analytical Hierarchy Process (AHP) Method Based on Java Netbeans in Midplaza Building - Hafiz, Muhammad Nur; Susano, Adhi; Frijuniarsi, Nurul (Yayasan Meira Visi Persada, 2024)
This research develops a decision support system for managing tenant work orders at MidPlaza Building using the Analytical Hierarchy Process (AHP) method based on Java Netbeans. This system is designed to assist building management in prioritizing and evaluating repair and maintenance requests from various tenants effectively and efficiently. By utilizing the AHP method, the system can analyze various criteria such as urgency, complexity and impact of each work order, thereby producing an objective priority ranking. Netbeans' Java-based implementation enables a user-friendly interface and ease of system maintenance. The research results show that this system can increase the efficiency of work order management, speed up response times, and increase tenant satisfaction at MidPlaza Building. This system integrates historical work order data, tenant information, and available resources to provide accurate and contextual recommendations. Key features include a real-time dashboard for monitoring work order status, an automatic notification system, and comprehensive analytical reports. The use of the AHP method allows flexibility in adjusting criteria weights in accordance with building management policies. Evaluation of system performance shows significant improvements in operational efficiency, with reduced work order completion times and increased levels of tenant satisfaction. This system also facilitates more optimal resource allocation and more effective budget management, helping building management make better decisions and be responsive to tenant needs.